Solid-State Transformer (S2T) of Single Phase Matrix Converter - Zafirah Zainuddin; Rahimi Baharom; Ihsan Mohd Yassin; Khairul Safuan Muhammad (Institute of Advanced Engineering and Science, 2018)
Solid-State Transformer (S2T) also known as Power Electronic Transformer (PET) is applied in various industrial fields compared to the conventional transformer due to it flexible voltage transfer ratio, high power density, and low harmonic distortion. This paper presents the S2T of Single Phase Matrix Converter (SPMC) that acts as cyclo-converter. A 1kHz frequency was synthesized on the primary side of the transformer using Pulse Width Modulation (PWM) technique, whilst, the output converted by the SPMC that produces the 50Hz frequency. A part of AC to AC operation, the switching algorithm for safe-commutation technique is also presented to solve the commutation problem caused by the usage of inductive load. Minimization of size, losses and optimal efficiency are the advantages of this approach. The proposed model was simulated by using MATLAB/Simulink (MLS).